Pengaruh Promosi dan Kepercayaan terhadap Keputusan Pembelian pada E-Commerce Tokopedia - Farah Annisa Salma; Saryadi Saryadi; Andi Wijayanto (Universitas Diponegoro, 2022)
Technology and information have developed today. This is marked by the many conveniences that can be obtained only by relying on technology. This is due to the effects of globalization, namely internet technology that makes it easier for people to carry out their daily activities anytime and anywhere. One of the other benefits of the internet is that it makes it easier for consumers to shop via online. It is easier for consumers to shop through the marketplace, one of which is Tokopedia. Tokopedia was ranked first in the